Arrhenius plot characteristics of membrane-bound 3-hydroxy-3-methylglutaryl coenzyme a reductase from the latex of hevea brasiliensis - Sipat, Abdullah B. (Elsevier BV, 1982)
The enzyme 3-hydroxy-3-methylglutaryl-CoA reductase (mevalonate:NADP+ oxidoreductase (CoA-acylating), EC 1.1.1.34) from the latex of regularly tapped trees of Hevea brasiliensis is membrane-bound. The effect of temperature on this enzyme was studied over the range of 8-40°C and the Arrhenius plot of activity showed a discontinuity at 14°C with an activation energy of 55.6 kJ/mol (13.3 kcal/mol) and 2.5 kJ/mol (0.6 kcal/mol) respectively above and below this temperature break. The result obtained is consistent with the known lack of fluidity of the membranes of the particles which the enzyme is associated with in the latex.